2016
DOI: 10.1097/hjh.0000000000000847
|View full text |Cite
|
Sign up to set email alerts
|

Plasma B-type natriuretic peptide concentration is independently associated with kidney function decline in Japanese patients with chronic kidney disease

Abstract: Higher BNP levels were associated with adverse renal outcomes, independent of cardiac structure and function, suggesting that BNP may be a useful biomarker for exploring factors associated with kidney disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…According to a previous study (2012 Kidney Disease: Improving Global Outcomes [KDIGO] Clinical Practice Guideline for the Evaluation and Management of CKD), CKD grade (G) was classified as follows: G1A2-3, eGFR ≥90 mL/min/1.73 m 2 and moderately to severely increased proteinuria; G2A2-3, 60≤eGFR<90 mL/ min/1.73 m 2 and moderately to severely increased proteinuria; G3aA1, 45≤eGFR<60 mL/min/1.73 m 2 and normal to mildly increased proteinuria; G3aA2-3, 45≤eGFR<60 mL/ min/1.73 m 2 and moderately to severely increased proteinuria; and G3bA1, 30≤eGFR<45 mL/min/1.73 m 2 and normal addition, several studies have demonstrated an association between progression of CKD and NT-proBNP or BNP. [8][9][10][11] Most of those studies, however, evaluated patients with CKD or renal insufficiency 8-10 and used BNP. 8,9 NT-proBNP is considered a more discerning marker than BNP to evaluate cardiac dysfunction.…”
mentioning
confidence: 99%
“…According to a previous study (2012 Kidney Disease: Improving Global Outcomes [KDIGO] Clinical Practice Guideline for the Evaluation and Management of CKD), CKD grade (G) was classified as follows: G1A2-3, eGFR ≥90 mL/min/1.73 m 2 and moderately to severely increased proteinuria; G2A2-3, 60≤eGFR<90 mL/ min/1.73 m 2 and moderately to severely increased proteinuria; G3aA1, 45≤eGFR<60 mL/min/1.73 m 2 and normal to mildly increased proteinuria; G3aA2-3, 45≤eGFR<60 mL/ min/1.73 m 2 and moderately to severely increased proteinuria; and G3bA1, 30≤eGFR<45 mL/min/1.73 m 2 and normal addition, several studies have demonstrated an association between progression of CKD and NT-proBNP or BNP. [8][9][10][11] Most of those studies, however, evaluated patients with CKD or renal insufficiency 8-10 and used BNP. 8,9 NT-proBNP is considered a more discerning marker than BNP to evaluate cardiac dysfunction.…”
mentioning
confidence: 99%
“…Studies have examined the relationship between plasma BNP level and renal function decline (1820). Recently, in a prospective CKD patient cohort of 372 participants, we found that a high plasma BNP level was associated with an increased risk for the incidence of ESRD with the need for renal replacement therapy or the doubling of serum creatinine after adjustment for clinical parameters, including cardiac structure and function (18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have examined the relationship between plasma BNP level and renal function decline (1820). Recently, in a prospective CKD patient cohort of 372 participants, we found that a high plasma BNP level was associated with an increased risk for the incidence of ESRD with the need for renal replacement therapy or the doubling of serum creatinine after adjustment for clinical parameters, including cardiac structure and function (18). Yasuda et al reported that, in 485 patients with CKD stage 3, 4, and 5, the plasma BNP level was significantly higher in patients who reached ESRD or the doubling of serum creatinine compared with those who did not (median [interquartile range]: 116 [51.5–318.0] ng/Lvs 53.7 [24.8–126.0] ng/L) (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several hospital-based studies have shown that serum NT-proBNP levels are associated with the progression of kidney impairment in patients with CKD. [15][16][17][18][19][20][21] However, only 3 community-based prospective studies have investigated the association of plasma BNP or serum NT-proBNP levels with the risk of CKD. [22][23][24] Moreover, no studies have addressed the potential use of serum NT-proBNP as a biomarker to improve the prediction of future onset of CKD.…”
mentioning
confidence: 99%